Determination age-related deficiency of functional movement proficiency and lower body strength in adolescent soccer players - Imal, O. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Quality of movement improves physical performance and reduces injury risk. It is known that biological maturation status (BMS) has a significant impact on the development of physical performance. However, strength development and functional movement (FM) competence show differences depending on BMS in adolescent soccer players. The goal of this study was to investigate the differences between different age categories (U13-U16) on FM proficiency and lower body strength (LBS) based on BMS of adolescent soccer players. METHODS: A sample of 79 male soccer players, aged 12,24 ± 0,26 to 15,21 ± 0,42 years, were recruited from a professional soccer club and examined into four age groups (U13, U14, U15 and U16). The Functional Movement Screen (FMS), counter movement jump (CMJ), squat jump (SQJ), counter movement jump free-arm (CMJ-FA) and isokinetic quadriceps/hamstring (Q/H) knee test by 60°s, 180°s, 300°s speeds were administered to assess FM proficiency and LBS based on peak height velocity (PHV) level of the individuals. Mirwald (2002), maturation offset was used to calculation of BMS, respectively. RESULTS: In this study, ANOVA showed a significant between-group effect in peak height velocity (PHV), FMS, isokinetic strength of Q/H (except H at 300°s), jump height (JH) of CMJ-FA, CMJ and SQJ and jump impulse relative of SQJ (p < 0.05). Along with this, there was found significant differences between older groups (U15, U16) and younger groups (U13, U14) in all the JH results of vertical jumps by ANOVA test (p < 0.05). When an ANCOVA was applied to account for the influence of biological maturation (PHV) on between-group differences, FMS and JH of all the jumps no longer displayed any significant differences between age groups. In addition, ANCOVA presented significant differences between older groups (U15, U16) and younger groups (U13, U14) in all the speeds of isokinetic strength (p < 0.05). Given that, PHV was found a significant covariate for all isokinetic strength tests, JH of CMJ-FA, CMJ and SQJ. CONCLUSION: The outcome of this study, FM competence and LBS methods were found to be affected differently depending on maturation. It was observed that vertical jump performance, which is a complex movement depending on maturation, did not change in direct correlation with FM, but isokinetic strength increased in the older groups depending on maturation. Moreover, biological age (PHV) was found one of the key indicators to observe whether any differences between age groups in FM proficiency and LBS. Future research should focus on developing targeted intervention studies within divided age groups according to PHV level of the players to improve FM quality and physical strength in the young population.